Phenotypic and genomic characterization of the first alkaliphilic aceticlastic methanogens and proposal of a novel genus Methanocrinis gen.nov. within the family Methanotrichaceae - Khomyakova, Maria A.; Merkel, Alexander Y.; Slobodkin, Alexander I.; Sorokin, Dimitry Y. (Frontiers in Microbiology, 2023)
Highly purified cultures of alkaliphilic aceticlastic methanogens were collected for the first time using methanogenic enrichments with acetate from a soda lake and a terrestrial mud volcano. The cells of two strains were non-motile rods forming filaments. The mud volcano strain M04Ac was alkalitolerant, with the pH range for growth from 7.5 to 10.0 (optimum at 9.0), while the soda lake strain Mx was an obligate alkaliphile growing in the pH range 7.7–10.2 (optimum 9.3–9.5) in the presence of optimally 0.2–0.3 M total Na+. Genomes of both strains encoded all enzymes required for aceticlastic methanogenesis and different mechanisms of (halo)alkaline adaptations, including ectoine biosynthesis, which is the first evidence for the formation of this osmoprotectant in archaea. According to 16S rRNA gene phylogeny, the strains possessed 98.3–98.9% sequence identity and belonged to the obligately aceticlastic genus Methanothrix with M. harundinaceae as the most closely related species. However, a more advanced phylogenomic reconstruction based on 122 conserved single-copy archaeal protein-coding marker genes clearly indicated a polyphyletic origin of the species included in the genus Methanothrix. We propose to reclassify Methanothrix harrundinacea (type strain 8AcT) into a new genus, Methanocrinis gen. nov., with the type species Methanocrinis harrundinaceus comb. nov. We also propose under SeqCode the complete genome sequences of strain MxTs (GCA_029167045.1) and strain M04AcTs (GCA_029167205.1) as nomenclatural types of Methanocrinis natronophilus sp. nov. and Methanocrinis alkalitolerans sp. nov., respectively, which represent other species of the novel genus. This work demonstrates that the low energy aceticlastic methanogenesis may function at extreme conditions present in (halo)alkaline habitats.